Integrated Infectious Disease and Substance Use Disorder Care for the Treatment of Injection Drug Use–Associated Infections: A Prospective Cohort Study With Historical Control. (21st December 2022) - Serota, David P; Rosenbloom, Liza; Hervera, Belén; Seo, Grace; Feaster, Daniel J; Metsch, Lisa R; Suarez, Edward; Chueng, Teresa A; Hernandez, Salma; Rodriguez, Allan E; Tookes, Hansel E; Doblecki-Lewis, Susanne; et al.
Abstract: Background: To address the infectious disease (ID) and substance use disorder (SUD) syndemic, we developed an integrated ID/SUD clinical team rooted in harm reduction at a county hospital in Miami, Florida. The Severe Injection-Related Infection (SIRI) team treats people who inject drugs (PWID) and provides medical care, SUD treatment, and patient navigation during hospitalization and after hospital discharge. We assessed the impact of the SIRI team on ID and SUD treatment and healthcare utilization outcomes. Methods: We prospectively collected data on patients seen by the SIRI team. A diagnostic code algorithm confirmed by chart review was used to identify a historical control group of patients with SIRI hospitalizations in the year preceding implementation of the SIRI team. The primary outcome was death or readmission within 90 days post–hospital discharge. Secondary outcomes included initiation of medications for opioid use disorder (MOUD) and antibiotic course completion. Results: There were 129 patients included in the study: 59 in the SIRI team intervention and 70 in the pre-SIRI team control group. SIRI team patients had a 45% risk reduction (aRR, 0.55 [95% confidence interval CI, .32–.95]; 24% vs 44%) of being readmitted in 90 days or dying compared to pre-SIRI historical controls. SIRI team patients were more likely to initiate MOUD in the hospital (93% vs 33%, P < .01), complete antibiotic treatment (90% vs 60%, P < .01), and less likely to have patient-directed discharge (17% vs 37%, P = .02). Conclusions: An integrated ID/SUD team was associated with improvements in healthcare utilization, MOUD initiation, and antibiotic completion for PWID with infections. Abstract : An integrated infectious disease/substance use disorder (SUD) team to treat injection-related bacterial and fungal infections was associated with a 45% decrease in readmission or death 90 days postdischarge. Additional benefits were demonstrated in antibiotic completion, SUD treatment, and patient-directed discharges.